Increased epoxyeicosatrienoic acids and reduced soluble epoxide hydrolase expression in the preeclamptic placenta. Issue 7 (July 2016) - Dalle Vedove, Francesco; Fava, Cristiano; Jiang, Houli; Zanconato, Giovanni; Quilley, John; Brunelli, Matteo; Guglielmi, Valeria; Vattemi, Gaetano; Minuz, Pietro
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Epoxyeicosatrienoic acids (EETs) derived from cytochrome P450 (CYP)-dependent metabolism of arachidonic acid are increased in the plasma of women with preeclampsia as compared with normal pregnancy and are significantly higher in fetal than in maternal plasma and erythrocytes. We hypothesized that differences in EET synthesis or metabolism in the feto-placental unit contributed to the observed differences in circulating EETs. Method: To evaluate EETs, formation as well as the expression of relevant CYP isoforms and the metabolizing enzyme, soluble epoxide hydrolase (sEH), biopsies of placenta were collected from 19 normal pregnancy and 10 preeclampsia at the time of cesarean section delivery. EETs were extracted from tissue homogenates and analyzed by liquid chromatography coupled with tandem mass spectrometry. Results: Both cis -EETs and trans -EETs were detected in the placenta. Concentration of total EETs was higher in the placenta from preeclampsia compared with normal pregnancy (2.37 ± 1.42 ng/mg vs. 1.20 ± 0.72 ng/mg, mean ± SD, P < 0.01), especially the 5, 6-, 8, 9- and 11, 12-EETs, measured in a subgroup of tissue samples (normal pregnancy = 10, preeclampsia = 5). By immunohistochemistry, sEH, CYP2J2, CYP4A11 were present in placental villi with different pattern distribution, whereas CYP2C8 was not detectable. Neither were CYP2J2, CYP4A11, and CYP2C8 detected in the umbilical cord. Western blot analysis of placenta homogenates showed reduced expression of sEH in preeclampsia as compared with normal pregnancy. Conclusion: Increased EETs in the placenta and umbilical cord are associated with the presence of CYP2J2, whereas reduced expression of sEH in preeclampsia may be the key factor of increased EETs in the placenta.